The Impact of Market Optimism and CEO Pay Disparity on Takeover Premium and Bidder Performance: Australian Evidence - Luong, Hoa Anh Thi (Curtin University, 2018)
The study explains the impact of market optimism and CEO pay disparity on takeover premium and bidder performance in Australia. The study finds that acquiring firms offer higher premiums when takeover deals are conducted in high market optimism or by CEOs with high pay disparity. The study suggests that bidder announcement returns can be explained by market sentiment, whereas CEO pay disparity and target selection are the possible explanation for bidder long-term performance.